(untitled) (Revista de Investigaciones Universidad del Quindío, 2013)
From the aerial parts of Mikania micrantha collected in Montenegro, Quindío (Colombia), were isolated the compounds: Acetyl-β-amyrin (1), Lupeol (2), Stigmasterol (3), Sesquiterpene lactones (SL) Mikanolide (4), Dihydromikanolide (5) Deoxymikanolide (6) and β-D-glucopyranoside of stigmasteryle (7). In order to compare the metabolic content, we studied a population collected in Paraíso-Guerrero (México), of the same species, obtaining the SL Xerantholide (8). Their structures were characterized by spectroscopic and chromatographic methods. Extracts and SL 4, 5 and 8 were tested against gram-positive bacteria (Staphylococcus aureus) and gram-negative (E. Coli, Pseudomona aeruginosa and Ralstonia solanacearum (race 2)). The results showed that the SL 8 percent inhibition was better than SL 4 and 5 against S. aureus and E. coli, while 4 exhibited a percentage of inhibition higher than 5 and 8 against Pseudomona aeruginosa.